COMPUTER-ASSISTED DRUG DESIGNING OF TRIAZOLE DERIVATIVE OF NOSCAPINE AS TUBULIN-BINDING ANTICANCER DRUG - Kumari, Puja; Dixit, Vineeta; Tiwari, Atul Kumar; Saxena, Saurabh; Vishvakarma, Naveen Kumar; Naik, Pradeep Kumar; Shukla, Dhananjay (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Microtubule-interfering drugs are commonly used to treat malignant disorders owing to indispensable role of this cytoskeletal element. These drugs include paclitaxel, docetaxel, and the Vinca alkaloids; however, owing to their non-selective action and overpolymerizing effects, these chemotherapy drugs are confounded by complications with serious toxicity (particularly, peripheral neuropathies, gastrointestinal toxicity, myelosuppression, and immunosuppression) (by taxanes) or depolymerizing effects (by Vincas) on microtubules. Thus, there is urgent need to explore novel tubulin-binding agents that are significantly effective and comparatively less toxic compared to currently available drugs for the treatment of human cancer. The current study focuses fusion of two novel anticancer compounds with low toxicity, i.e., noscapine and triazole to generate a new ligand derivative. Methods: Using computer-aided drug designing approach and molecular docking, molecular interaction of these derivatives with αβ-tubulin heterodimer was confirmed and investigated by molecular docking along with dynamics simulation. Results: A greater affinity of the newly designed ligands for binding to tubulin was predicted. The predictive binding free energy (Gbind,pred) of these derivatives (ranging from −10.5178 to −16.8473 kcal/mol) based on linear interaction energy method with a surface generalized born continuum salvation model showed improved binding affinity with tubulin as compared to the lead compound. natural α-Noscapine (−5.505 kcal/mol). The binding energy of ligand determined using LigX, i.e., MM/GBVI was found to be −23.208 kcal/mol. Conclusion: We found that designed derivative compounds have better efficacy as compared noscapine and triazole.